The Influence of Employer Attractiveness and Company Reputation on the Intention of Applying for Jobs in Startup Companies in Final Level Students of Universitas Telkom - Ardiansyah, Fredy; Sary, Fetty Poerwita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to determine the effect of employer attractiveness on the intention to apply for work in startup companies and company reputation on the intention to apply students for work in startup companies among Universitas Telkom final-year. This research uses a quantitative approach. The data collection method was carried out by distributing questionnaires to 251 respondents as a sample of the total population of 7622 Universitas Telkom final-year students. The results of this study indicate that employer attractiveness and company reputation each have a positive and significant effect on job application intention. The company reputation variable also has a greater influence than the company reputation variable.